Biostratigraphy and taxonomy of fusulinid foraminifera across the Upper Mississippian (upper Serpukhovian)–Lower Pennsylvanian (Bashkirian) successions from the Hadim Nappe, Central Taurides, southern Turkey. (May 2021) - Akbaş, Melikan; Okuyucu, Cengiz
Abstract: The Hadim Nappe, which is one of the allochthonous tectonic units in the Tauride Belt, in southern Turkey, includes a continuous stratigraphic succession from the Middle(?)–Late Devonian to Late Cretaceous. A relatively complete succession of the upper Serpukhovian to Bashkirian is exposed in the Central Taurides, where two sections (Yassıpınar and Gölbelen) have been selected for detailed biostratigraphic investigations. The Mississippian-Pennsylvanian boundary in these sections was determined by the first appearance datum of the Plectostaffella jakhensis and located in the oolitic limestone facies indicating a shallow-water depositional environment. The uppermost Serpukhovian and regional Bashkirian substages (Syuranian, Akavasian, Askynbashian, and Arkhangelskian) were determined by index taxa, namely Plectostaffella jakhensis, P . bogdanovkensis, P . varvariensis, Pseudostaffella antiqua, Staffellaeformes staffellaeformis, Tikhonovichiella tikhonovichi, and Verella spicata . Fifty fusulinid species belonging to fourteen genera were determined in two sections, in which two species are new: Depratina turani Akbaş new species and Tikhonovichiella praetikhonovichi Akbaş new species. The taxonomic positions of two fusulinid species ( Depratina convoluta n. comb. and Staffellaeformes parva robusta n. comb.) are revised. The studied fusulinid assemblages correlate with fusulinid assemblages from the southern Urals, Russian Platform, Donetz Basin, Darvaz, Spain, central Iran, and some other regions of the Tethyan Realm. UUID: http://zoobank.org/bcbb6c72-f6f9-4e77-9cf9-3572bd731ff3